2022
DOI: 10.1007/s12671-022-02018-y
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Parenting Mediated Between Mothers’ Perceived Stress During COVID-19 and Child Adjustment

Abstract: Objectives Maternal stress is associated with a myriad of maladjusted outcomes among children. To identify the role of mindful parenting between mothers’ stress and child adjustment during the COVID-19 pandemic, this study tested competing hypotheses with mothers’ mindful parenting as a mediator versus a moderator. Methods A total of 172 Chinese mothers of preschool-aged children participated in this study. Participants completed a self-report measure of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Mothers' stress during this challenging period manifests in child adjustment issues, spanning internalizing problems, externalizing problems, and prosocial behaviors. Remarkably, mindful parenting acts as a mediating force, attenuating the impact of maternal stress on child adjustment, thereby underscoring its resilience-enhancing role [39]. This mediation extends to various dimensions, including prosocial behavior, externalizing problems, and internalizing problems, establishing mindful parenting practices as pivotal contributors to navigating challenging circumstances.…”
Section: The Association Between Mindful Parenting and Prosocial Beha...mentioning
confidence: 98%
“…Mothers' stress during this challenging period manifests in child adjustment issues, spanning internalizing problems, externalizing problems, and prosocial behaviors. Remarkably, mindful parenting acts as a mediating force, attenuating the impact of maternal stress on child adjustment, thereby underscoring its resilience-enhancing role [39]. This mediation extends to various dimensions, including prosocial behavior, externalizing problems, and internalizing problems, establishing mindful parenting practices as pivotal contributors to navigating challenging circumstances.…”
Section: The Association Between Mindful Parenting and Prosocial Beha...mentioning
confidence: 98%
“…25 In Indonesia, new rules have been implemented to reduce the spread of the COVID-19 virus 26 , one of which is the 14-day quarantine rule for those coming from outside the city or abroad who are affected by COVID-19. 27 The community consciously obeys this policy for the sake of collective health. 28 One interesting story is a husband and wife who had to get married online because the husband-to-be, Kardiman bin Haeruddin, had to undergo quarantine after traveling from a city exposed to COVID-19 cases.…”
Section: Phenomenon In Online Marriage During Covid-19 Pandemicmentioning
confidence: 99%
“…When parents experience significant parenting or nonparenting stress, they are prone to lapses in mindful attention during interactions with children and so are more likely to rely on automatic hostile, coercive, and ineffective parenting behavior (Cheung & Wang, 2022; Parent et al, 2021). By contrast, research has found that mindful parenting is conducive to parent–child interactions and lessens both parenting and nonparenting stress (Corthorn & Milicic, 2016; Fernandes et al, 2021; Moreira & Canavarro, 2018).…”
Section: Overview Of the Intergenerational Transmission Model Of Self...mentioning
confidence: 99%